Rebels of the heavenly kingdom - Paterson, Katherine (New York : Puffin Books, 1995)
Abducted from his home by bandits, fifteen-year-old Wang Lee is rescued from slavery by a mysterious girl who introduces him to the Taiping Tienkuo, a secret society partly based on Christian principles and dedicated to the overthrow of the Manchu government.
"First published in the U.S. by Lodestar Books, E.P. Dutton, Inc., 1993"--T.p. verso.
Booklist.
Five Owls.
School Library Journal.
6.5
7-9
Keywords: China -- History -- Taiping Rebellion, 1850-1864 -- Juvenile fiction; China -- History -- Foreign intervention, 1857-1861 -- Fiction; China -- History -- Taiping Rebellion, 1850-1864 -- Fiction; China -- History -- Fiction